The Influence of Organizational Culture and Motivation on Employee Performance on Esas Management Jakarta - Eris Sutrisna (Management Analysis Journal, 2023)
The purpose of the study was to test and analyze the influence between the variables of organizational culture (X1) and motivation (X2) with the kinerjja of PT Esas Management Jakarta employees. Data collection was carried out through the dissemination of questionnaires and was carried out on 43 employees. Data analysis in this study used descriptive analysis and regression analysis in conjunction with two free variables (X1 and X2) and one bound variable (Y). Questionnaire item testing uses validity and reliability tests to test the reliability of questionnaire question items. A classical assumption test that includes a normality test, a multicholinearity test, which is performed to obtain the feasibility of a regression model. While the purpose of this study is to answer the hypothesis in the f test and t test. The results of the validity and reliability test show that all statements of each variable state that they are valid and reliable. Based on the results of data analysis together, organizational-culture and motivassi have a significant effect on the performance of PT Esas Management employees with a value of 0.772 or 77.20%.